2020
DOI: 10.1099/mic.0.000910
|View full text |Cite
|
Sign up to set email alerts
|

Multigenic engineering of the chloroplast genome in the green alga Chlamydomonas reinhardtii

Abstract: The chloroplast of microalgae such as Chlamydomonas reinhardtii represents an attractive chassis for light-driven production of novel recombinant proteins and metabolites. Methods for the introduction and expression of transgenes in the chloroplast genome (=plastome) of C. reinhardtii are well-established and over 100 different proteins have been successfully produced. However, in almost all reported cases the complexity of the genetic engineering i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…SDS polyacrylamide gel electrophoresis was used to fractionate the cell lysates, which were then probed using an antibody against the HA epitope. Western blot analysis confirmed that the four colonies analysed produced the recombinant enzyme (Figure 4C), although levels were markedly lower than that seen for a control transformant engineered to make an HA-tagged serine protease (SplB) [54]. A transformed line lacking any transgenic coding sequence was used as a negative control.…”
Section: Expression Of the Anf /Nif Genes In The Chloroplast Of C Reinhardtiimentioning
confidence: 82%
See 2 more Smart Citations
“…SDS polyacrylamide gel electrophoresis was used to fractionate the cell lysates, which were then probed using an antibody against the HA epitope. Western blot analysis confirmed that the four colonies analysed produced the recombinant enzyme (Figure 4C), although levels were markedly lower than that seen for a control transformant engineered to make an HA-tagged serine protease (SplB) [54]. A transformed line lacking any transgenic coding sequence was used as a negative control.…”
Section: Expression Of the Anf /Nif Genes In The Chloroplast Of C Reinhardtiimentioning
confidence: 82%
“…Hence, the algal chloroplast is increasingly being recognised as a potential site for light-driven metabolic engineering [36]. Recent studies reporting the expression of multiple transgenes from the plastomes of both C. reinhardtii [53,54] and tobacco [43] demonstrate that complex genetic engineering, such as that required for the introduction of multi-step metabolic pathways or multi-subunit enzyme complexes, is feasible within the chloroplast. Currently, the main technical challenges for the successful expression of a set of nif genes in the C. reinhardtii chloroplast relate to the need for advanced synthetic biology (SynBio) tools: namely, (i) a need for a standardised DNA assembly method that would allow a rapid SynBio approach to the building and testing of multiple transgene configurations, and (ii) an increased number of validated regulatory DNA parts and inducible mechanisms for tuneable regulation of these transgenes.…”
Section: The Chlamydomonas Chloroplast As a Testbedmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the case of chloroplast expression, a series of vectors optimized with specific promoters and UTRs have been described [ 172 , 173 ]. A remarkable example is the use of photorestoration systems in which the use of selectable markers is avoided since the strain carries a mutation that abolish photosynthesis, which is restored upon the foreign DNA insertion that contains the functional gene [ 174 ]. Moreover, inducible expression systems have been developed for the chloroplast and constitute a promise for the field (especially when the target biopharmaceutical exerts toxic effects in the algae species used as host) [ 175 ] to separate the growth phase from the expression phase as requirement to maximize production.…”
Section: Algae-made Biopharmaceuticalsmentioning
confidence: 99%
“…As these photosynthetic microbes contain chloroplasts, which have their own genomes, called the plastome, they can be manipulated to introduce foreign genes for overproduction and also to introduce enzymes that can alter chloroplast metabolism to produce new chemicals [8]. In this work the authors assemble multigene constructs and are able to move them in a single event onto the chloroplast genome, being able to detect synthesis of the products of all three genes they introduced at once [9]. While promising, they also note that care must be taken in designing the regulatory elements for each separate transcriptional unit and they see recombination between 3′UTRs when they are very similar.…”
mentioning
confidence: 99%